Dychotomy “own–alien” in the novel “She: The Sixth Door” by I. Rozdobudko in the historiosophical aspect (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
On the example of the novel by I. Rozdobudko "She: The Sixth Door", the article analyzes the opposition "own-alien" as one of the aspects of the implementation of the historiosophical concept of the author. In particular, is explored the contrast between imaginary and real worlds. The first of them is an incarnation of alien, unacceptable and hostile space, and the second – the personification of safety and comfort.
Keywords: historiosophy; dichotomy; archetype; space; model of the world; the real world; the unreal world